Comparison of Oblique Lateral Interbody Fusion (OLIF) and Minimally Invasive Transforaminal Lumbar Interbody Fusion (MI-TLIF) for Treatment of Lumbar Degeneration Disease: A Prospective Cohort Study. Issue 6 (15th March 2022) - Zhu, Hai-Feng; Fang, Xiang-Qian; Zhao, Feng-Dong; Zhang, Jian-Feng; Zhao, Xing; Hu, Zhi-Jun; Fan, Shun-Wu
Abstract : A prospective cohort study is underway to evaluate the difference of oblique lateral interbody fusion (OLIF) and minimally invasive transforaminal lumbar interbody fusion with respect to perioperative data, patient-reported outcomes, radiographic measure, and complications. The results demonstrate surgeons could give preference to OLIF on the basis of a rich experience in lumbar anatomy and lumbar anterior or lateral surgery. Abstract : Study Design: Prospective cohort study. Objective: To assess the differences in the clinical and radiological outcomes between oblique lateral interbody fusion (OLIF) and minimally invasive transforaminal lumbar interbody fusion (MI-TLIF). Summary of Background Data: Nowadays, there is still a controversy regarding whether OLIF is superior to MI-TLIF in the management of degenerative lumbar disease. Methods: Between August 3, 2019 and February 3, 2020, 137 patients were assigned to OLIF or MI-TLIF at their request and the surgeon's discretion: 71 in the OLIF group and 66 in the MI-TLIF group. The perioperative data, patient-reported outcomes, radiographic outcomes, and complications were compared between the two groups. Results: The OLIF group showed shorter operation time (110.5 vs. 183.8 minutes, P  < 0.001), lesser estimated blood loss (123.1 vs. 232.0 mL, P  < 0.001), shorter length of hospital stay (5.5 vs. 6.7 days, P  < 0.001), and lower serum creatine kinase (CK) (1 day postoperatively) (376.0 vs. 541.8 IU/L, P  < 0.01) than that of MI-TLIF group. Both groups showed no significant differences in the visual analog scale (VAS) scores of lower back and leg pain and the Oswestry Disability Index (ODI) scores preoperatively and at 1, 3, and 12 months postoperatively, respectively ( P  > 0.05). Compared with the MI-TLIF group, the OLIF group showed better restoration of disc height (DH) (4.7/4.6/4.7 vs. 3.7/3.7/3.7 mm, P  < 0.01) and lumbar lordosis angle (LLA) (10.5°/10.8°/11.1° vs. 5.8°/5.7°/5.3°, P  < 0.001), but not the value of segmental lordosis angle (SLA) ( P  > 0.05) at 1 day, 1 month, and 1 year postoperatively, respectively. The complication rate of OLIF was higher than that of MI-TLIF (29.4% vs. 9.7%, P  < 0.01). Conclusion: Compared with MI-TLIF, OLIF showed similar results in terms of patient-reported outcomes, restoration of SLA and fusion rate, and superior results with respect to restoration of DH and LLA, operation time, estimated blood loss, length of hospital stay, and serum CK levels (1 day postoperatively). Even though the complication rate of OLIF is higher than that of MI-TLIF, it does not bring persistent and substantial damage to the patients. Level of Evidence: 3